THE LEVELS OF DEMOCRATIC AND SCIENTIFIC VALUES OF 8TH GRADE SECONDARY SCHOOL STUDENTS - Tümen, Tuğba; Bahçeci, Ferhat (My University, 2020)
Values are the guiding patterns of behavior that ensure the integrity of a society. In order for theindividual to be a part of the society to which they belong, these behavior patterns should betransferred. Family, school and society play a role in the transfer of values. In this study, thevalues of democratic and scientific perspectives to 8th grade students in a province in Turkey hastried to determine. In order to determine the values, the scale of democratic and scientific valuesand demographic information form developed by Akbaş (2004) were used. The universe of theresearch consists of 8th grade students of secondary school studying in the 2018-2019 academicyear. The sample, on the other hand, consists of 245 8th grade students from 4 secondary schools.Descriptive survey model was used in the research. As a result of the applied statisticalcalculations, the effects of variables such as gender, education levels of parents and economicstatus of the family were examined. In order to determine whether these variables show normaldistribution, normality analysis was performed on the data of the variables using theKolmogorov-Smirnov test. As a result of the analysis, it was seen that the scientific values scaleshowed normal distribution, while the democratic values scale did not show a normaldistribution. Therefore, non-parametric tests were used in the analysis of the sub-problems ofthe democratic values scale. In addition, as a result of the reliability analysis, the Cronbach'sAlpha value of the democratic values scale was found to be .83, and the Cronbach's Alpha valueof the scientific values scale was found to be .84. As a result of the research, a significantdifference was found in the gender variable in scientific and democratic values. Parents'education level and income level variables did not cause a significant difference on democraticand scientific value scores. The significant difference in the opinions of the participants wastested at the .05 level.
Keywords: Etik; Eğitim; Eğitim Araştırmaları; Sosyoloji